Metamaterials - Devices and Applications 2017
DOI: 10.5772/67198
|View full text |Cite
|
Sign up to set email alerts
|

Active and Tunable Metamaterials

Abstract: In this chapter, we will first present the research progress on the active and tunable meta materials based on different realization methods, such as varactor diodes, liquid crystals, superconductivity, and structural-shifting structures. Then we focus on the achievements in our research group for the tunable metamaterials by using the ferrite as the substrate of metamaterials. We will present the designs and theories of single-, dual-, and tripleband tunable metamaterials based on the ferrite and the design o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
(119 reference statements)
1
1
0
2
Order By: Relevance
“…Meanwhile, PLLA has quite a slow spherulite growth. As expected, the similar periodic patterns were reported recently in low molecular weight PLLA thin films both from melt-crystallization and vapor-assisted crystallization [27,41,42]. It can, therefore, be concluded from the above findings that it is the crystallization condition rather than the structural feature that is important to determine the stacking mode of radial lamellae in polymer spherulites.…”
Section: Manipulating the Stacking Of Radial Lamellae To Prepare Concsupporting
confidence: 89%
See 1 more Smart Citation
“…Meanwhile, PLLA has quite a slow spherulite growth. As expected, the similar periodic patterns were reported recently in low molecular weight PLLA thin films both from melt-crystallization and vapor-assisted crystallization [27,41,42]. It can, therefore, be concluded from the above findings that it is the crystallization condition rather than the structural feature that is important to determine the stacking mode of radial lamellae in polymer spherulites.…”
Section: Manipulating the Stacking Of Radial Lamellae To Prepare Concsupporting
confidence: 89%
“…Shao et al found a polymorphic transition of polybutene-1 via chloroform and water vapor annealing [40]. Using a similar PLLA film-chloroform system, an unusually-banded pattern that is distinct from that of melt crystallization was also produced [41,42]. More spherulites of the same crystallizable object were observed via an evaporative crystallization procedure [43].…”
Section: Introductionmentioning
confidence: 99%
“…Известно, что метаматериалы представляют собой искусственно созданные среды со свойствами, не встречающимися у обычных природных сред [1]. Среди метаматериалов особый класс составляют дважды отрицательные среды (или " левые" среды), у которых диэлектрическая ε и магнитная µ проницаемости являются одновременно отрицательными величинами [2].…”
unclassified
“…Помимо создания дважды отрицательных сред на основе ФМ, работающих в микроволновом диапазоне, были предприняты попытки создать аналогичные среды и функциональные устройства для терагерцевого диапазона [1,[11][12][13]. Так, в [14] было проведено численное моделирование показателя преломления метаматериала, выполненного на основе ферритовых пленок LuBiIG и серебряных полосок, который имел отрицательные значения на частотах выше 100 GHz.…”
unclassified